2017
DOI: 10.5194/gmd-10-1209-2017
|View full text |Cite
|
Sign up to set email alerts
|

The Met Office HadGEM3-ES chemistry–climate model: evaluation of stratospheric dynamics and its impact on ozone

Abstract: Abstract. Free-running and nudged versions of a Met Office chemistry-climate model are evaluated and used to investigate the impact of dynamics versus transport and chemistry within the model on the simulated evolution of stratospheric ozone. Metrics of the dynamical processes relevant for simulating stratospheric ozone are calculated, and the free-running model is found to outperform the previous model version in 10 of the 14 metrics. In particular, large biases in stratospheric transport and tropical tropopa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 63 publications
(68 reference statements)
5
45
0
Order By: Relevance
“…2a and b). This effect is consistent with previous work that has shown that transport controls lower stratospheric ozone concentrations Hartmann, 1981;Rood and Douglass, 1985;Hartmann and Garcia, 1979;Silverman et al, 2018). The CCMI ensemble-mean (i.e., the mean of all 42 submodels) correlation between March ASO and March geopotential height and temperature is shown in Fig.…”
Section: Effect Of Arctic Stratospheric Ozone (Aso) On Polar Surface supporting
confidence: 92%
“…2a and b). This effect is consistent with previous work that has shown that transport controls lower stratospheric ozone concentrations Hartmann, 1981;Rood and Douglass, 1985;Hartmann and Garcia, 1979;Silverman et al, 2018). The CCMI ensemble-mean (i.e., the mean of all 42 submodels) correlation between March ASO and March geopotential height and temperature is shown in Fig.…”
Section: Effect Of Arctic Stratospheric Ozone (Aso) On Polar Surface supporting
confidence: 92%
“…observations at a specific location, we expect that chemical transport models (CTMs) or CCMs with specified dynamics (CCM-SD) would be more accurate in capturing the O 3 variability and other dynamical variables than free-running CCMs; this has been demonstrated in previous studies (e.g. Hardiman et al, 2017). This could have implications for projecting long-term future O 3 trends using free-running CCMs.…”
Section: Ozone Trendsmentioning
confidence: 78%
“…Therefore, careful evaluations of free-running CCMs are needed. However, Hardiman et al (2017) also find that tropical upwelling and the stratospheric meridional circulation are difficult to constrain and are worse in the nudged simulations than in the free-running simulations. Here, we aim to attribute observed O 3 trends to various chemical and dynamical processes, and we consider that free-running CCMs are the more suitable models to be used in such study.…”
Section: Ozone Trendsmentioning
confidence: 88%
“…As such, they are valuable tools for studying climate change on decadal to centennial timescales (e.g. Collins et al 2011;Gent et al 2011;Martin et al 2011;Hazeleger et al 2012;Flato et al 2013;Hurrell et al 2013;Hardiman et al 2017). However, these models are extremely computationally expensive.…”
Section: Introductionmentioning
confidence: 99%